Degree Equitable Connected Domination in Fuzzy Graphs - M. Rani, K.M. Dharmalingam (Asian Journal of Current Engineering and Maths, 2015)
Let be a fuzzy graph. Let and be two vertices of . A fuzzy connected dominating set is to be a fuzzy equitable connected dominating set if for every there exists a vertex such that and where denotes degree of vertex and denotes the degree of vertex and . The minimum cardinality of fuzzy equitable connected domination set is denoted by . In this paper we introduce the concept of fuzzy equitable connected dominating set. Also we obtain some interesting results for this new parameter in equitable connected domination in fuzzy graphs.